Constitution Building, Constitutionalism and National Values: Whither Ghana? - Quashigah, E. (University of Ghana, 2016)
My teaching and research interests include Jurisprudence, Constitutional Law, Human Rights, International Humanitarian Law, Governance, Elections Law and Alternative Dispute Resolution and this lecture represents a synthesis of my ideas formed over the years of study and research. The republican state assumes that those who govern are exercising powers in trust for the people and are therefore expected to exhibit the highest level of trust expected. It is to curb the potential abuse of this sacred trust that constitutions are formulated to guide towards constitutionalism. However experience has taught us that the existence of a constitution and the practice of constitutionalism are not necessarily the same. The existence of a constitution is a practical fact but the practice of constitutionalism is essentially one of values demonstrated in actual practice. A person can strictly conform to the constitutional provisions and therefore be within the law, but at the same time operate completely outside of the expectations of constitutionalism. Constitutionalism understood merely as a system in which the constitution limits the powers of government is self deception; constitutionalism is a matter of values; values that clothe the bare constitutional skeletons and thereby make possible a system of government that would be truly representative, not merely because the people voted for it to win political power, but because it is operating according to the inherent values upon which the country is built; values that are known and accepted by all and are non-negotiable. These would form the standards according to which we could judge all of us, particularly those who exercise the powers of the State. We have observed various governments exercise powers that otherwise were lawful, but which were without regard to the sensitivities of the generality of the people or the inherent interests of the fundamental principles upon which the nation is built. Examples exist in almost all the various regimes Ghana has experienced. It is this attitude that brings us to the issue of values that must be developed tosupport the exercise by individuals of the powers of the State conferred on them. Within a period of fifty years Ghana has tried its hands at all kinds of governmental systems including a still born idea of a Union Government. Yet we still hunger for changes, as was reflected in the most recent Constitution Review Commission exercise. Irrespective of all these efforts at strengthening our constitutional governance through the strengthening of constitutional institutions we continue to experience behaviour that do not demonstrate respect for fundamental values expected of people who aspire to promote the best system of governance to protect the welfare of the people. The constitutional history of Ghana is replete with evidence of executive behaviour and also individual actions that do not exhibit any indication of some acceptable values in conformity with the inherent principles of the particular constitutions. It is the proposal that there is the need for a national conference to develop a national charter on national values and how to inculcate them into our political and social psyche. We need to consciously develop positive features articulated as political and social characteristics that would identify or set us out as Ghanaians. We cannot leave it to political leaders to determine because they have demonstrated that by the nature of their operations they still have a lot to learn about the nature of the trust that they seek to take up – take the following news report for example: “NPP has no monopoly over violence in A/R – NDC: The ruling National Democratic Congress (NDC) in the Ashanti Region has served a strong warning to the opposition New Patriotic Party (NPP) that it has no monopoly over violence in the region and therefore should not extend its violent conduct to them. Deputy Regional Secretary of the NDC Kwame Zu at a press conference on Sunday disclosed that the party’s refusal to reply the NPP in equal measure was not a manifestation its members are weak and cowards.” (Source: Ghanaweb, Sunday, 1 May 2016.) We cannot also leave it to religious organizations because they have lost the opportunity long ago. I wonder if even we the academics, the technocrats and men and women in business and industry can claim that we have the clear conscience to preach values to others. I believe we can only go back to the beginning, the meeting of all at the lowest levels, the source of primal political and social authority which we in a way recognized in our constitution when we proclaimed in the Constitution that Sovereign authority resides in the people. It is only by conscious conscientization through the inscription of acceptable national values that citizens can hope to have, and hold accountable, leaders who should utilize the powers of government for the real purpose for which they are conferred. Otherwise such a nation will continue to wobble and its citizens held hostage by its leaders. With the right values and a conscientized citizenry the constitutional provisions as they are could achieve their intended objectives; but with the wrong values even the most sophisticated constitutional provisions will fail in their inherent objectives. This is why I call for a consciously created and integrated core of values that are needed to support our constitution. I want to believe that the problem is not a lack of values, because the 1992 Constitution, the National Anthem, the National Pledge and other similar sources contain a myriad of values. The problem is a lack of ownership and an appreciation of the values we have. It is the conviction that until we take the conscious step to make these values owned by the citizenry they will continue to mean nothing and their application of the constitution would be bereft of the influence of these values. What we actually need therefore is not a Constitution Review Commission but a National Values Identification and Actualization Commission (NVIAC); this should be a commission that should work from the community level up to the national level to deduce the values that should become synonymous with being a Ghanaian. That commission should also work to ensure that those values are owned by all Ghanaians. That is the way forward if the constitution is to be understood and operated as a sacred charge to all Ghanaians and according to which values we can sanction our political leaders and ourselves. Ghana needs a National Idea.
Keywords: Constitution Building; Constitutionalism; National Values; Ghana